The Union Perspective of the Implementation of Industry 4.0: The Case of Mercedes-Benz - Martins, Fernando Ramalho; Muniz Jr, Jorge [UNESP]; Santos, Joao Paulo de Oliveira [UNESP] (Assoc Nac Cursos Graduacao & Administracao, 2023)
Organizational and technological innovations constantly challenge decision makers and the roles played by them. This is the background of the teaching case on screen. Based on the report of labor representatives, it aims to present a dilemma imposed by an adverse industrial context that feels the creativity and flexibility of decision makers, whether from the organization or from the labor representation bodies. In this way, students will have to act as organizational or union leadership so that they develop their creative thinking and find innovative solutions that often challenge the roles traditionally played by organizational agents. The dilemma that presents itself implies the need for teamwork and the ability to create consensus. The case privileges a point of view not always emphasized in the academic world, the trade union point of view.
Keywords: Innovation; change; decision making; trade unionism